1994
DOI: 10.1164/ajrccm.149.5.7513595
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin-induced airway obstruction in tracheally perfused guinea pig lungs.

Abstract: The neurokinin receptors responsible for transducing the airway obstruction resulting from capsaicin infusion were defined in the tracheally perfused guinea pig lung. In this lung preparation, buffer is perfused via the trachea and allowed to exit the lung through numerous small holes in the pleural surface; airway obstruction is monitored as the backpressure (Pao) generated at a constant perfusion flow rate. Infusion of the specific NK1 receptor agonist, Sar-9 Met02(11) substance P, resulted in an increase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In human airways, contractile responses to capsaicin and SP and NKA are thought to be mediated through the NK 2 receptor (Naline et al , 1989; Ellis et al , 1993). In guinea‐pig trachea, stimulation of both NK 2 and NK 1 receptors are thought to mediate the bronchoconstrictor response to capsaicin (Bertrand et al , 1993; Lilly et al , 1994) and the related compound resiniferatoxin (Foulon et al , 1993), although NK 2 receptor mediated pathways appear to predominate (Mizuguchi et al , 1996). In the present study, contractile responses to NKA were significantly greater than those elicited by the selective NK 1 receptor agonist, [Sar 9 ,Met(O 2 ) 11 ]‐SP.…”
Section: Discussionmentioning
confidence: 99%
“…In human airways, contractile responses to capsaicin and SP and NKA are thought to be mediated through the NK 2 receptor (Naline et al , 1989; Ellis et al , 1993). In guinea‐pig trachea, stimulation of both NK 2 and NK 1 receptors are thought to mediate the bronchoconstrictor response to capsaicin (Bertrand et al , 1993; Lilly et al , 1994) and the related compound resiniferatoxin (Foulon et al , 1993), although NK 2 receptor mediated pathways appear to predominate (Mizuguchi et al , 1996). In the present study, contractile responses to NKA were significantly greater than those elicited by the selective NK 1 receptor agonist, [Sar 9 ,Met(O 2 ) 11 ]‐SP.…”
Section: Discussionmentioning
confidence: 99%
“…, 1988). The predominant mechanism in capsaicin‐ or resiniferatoxin‐induced airway obstruction occurs indirectly through the stimulation of the tachykinin NK 2 ‐receptors in perfused isolated lung (Lilly, Besson, Israel, Rodger & Drazen, 1994) or intact guinea‐pig (Satoh, Lou, Lee & Lundberg, 1992; Foulon et al. , 1993; Kudlacz, Logan, Shatzer, Farrell & Baugh, 1993; Boni, Ballati & Evangelista, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Tracheal perfusion assays were used to define the functional capacity of the tachykinin receptors present in our samples. Because of the limited number of samples available for study, we chose to use substantial doses of agonists that had been previously demonstrated to be effective in causing bronchoconstriction in the tracheal perfusion model (31)(32)(33). In our studies, tracheal perfusion assay of capsaicin-challenged lungs demonstrated that the midgestational (i.e., canalicular stage) developing lung can release endogenous neuropeptides that activate neurokinin receptors on smooth muscle to cause bronchoconstriction.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the limited number of samples available for the tracheal perfusion studies, doses for the peptide agonists and SR-48968 were chosen from published studies examining human and animal model airway responses. Doses used in the tracheal perfusion assays were those that caused bronchoconstriction in adult guinea pig samples studied with tracheal perfusion assay (31,32) and those demonstrated to be effective bronchoconstricting doses in other models (13,48,63). At the completion of the assays, the intact capacity of the pulmonary smooth muscle to respond to agonists was demonstrated by administering 6.1 mg (0.025 mol) of the nonspecific smooth muscle agonist BaCl 2.…”
Section: L1349mentioning
confidence: 99%